A Case Study Illustrating Coding for ComputationalThinking Development (International Conference on Computers in Education, 2016)
Previous studies suggested that computational thinking is an important skill that schools should start equipping children with from primary school education. This study proposes way to develop a mobile app coding curriculum in primary 4 to 6 to nurture students’ computational thinking. It will guide students to undergo learning stages from developing their own codes and combining with others’ work to create their own apps and staging their apps to gain confidence and recognition of performance in coding. An example of mathematic game in the curriculum is selected as a case study to illustrate in this study how it incorporates the elements of computational thinking in the coding activities progressively. It is believed that the proposed way of curriculum development paves a learning path which may drive students’ interest in coding and students could develop computational thinking skills progressively